Adopting a pavement management system (PMS) for local governments - Domingo, Razon C.
Many developed countries have been and even developing countries are now implementing pavement management system (PMS) to effectively and efficiently manage their highway or road pavements. The Philippine Department of Public Works and Highways will be adopting the HDM-4 tool for its PMS. However, the shortage of funds for maintenance of road infrastructures is also a problem in the local government level and therefore the need for a pavement management system arises. A simple PMS is developed for implementation at the local governments. The PMS is composed of techniques on how to prioritize road maintenance projects and a preventive maintenance program. A knowledge-base expert system (KBES) application software is also developed for data storage and analysis to complement the manual distress data collection survey. In the road prioritization strategy, the pavement condition index (PCI) is used which rates the pavement condition according to the severity and extent of distress types present. Before the calculation of PCI, each distress attribute must be assigned a distress weight, severity and extent weight. A statistical algorithm is presented which converts the subjective rating scores of distress attributes from experts to a rational weighting scale that provides quantified measurement of the effects of each distress on pavement damage and riding quality. In the pavement preventive maintenance strategy, the timing of application of maintenance treatments is presented which is also based on the opinions of experts and engineers. These strategies are both contained in the application software. The application software was validated by conducting actual surveys and the results proved to be consistent with that of pavement expert in recommending maintenance treatments.